Dialog muzyczny dziecka i nauczyciela w przedszkolu = The child and teacher`s musical dialogue in kindergarten - Kisiel, Mirosław (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The paper focuses on the issues of the child and teacher remaining in the musical dialogue, seen as a process in the area of raising a child in kindergarten.
Keywords: dialog muzyczny; dziecko; nauczyciele; przedszkole; dialog music; child; teacher; kindergarten